Configuration and Charge Dynamics of Defect‐Cluster‐Dipoles in CaTiO3 for Enhanced Permittivity - Wang, Jian; Zou, Zhuowen; Zhu, Jiajun; Gao, Dandan; Hu, Wanbiao (Advanced electronic materials, 2025)
The wealth of complex defects induces attractive functionalities and structural variations in materials. This renders engineering defect states, as well as building up a defect‐property relationship, a central subject, but it remains highly challenging because the configurations and charge dynamics of the involved defect systems are hardly explored and thus unclear experimentally. Herein, the defect‐dipole‐cluster in La‐doped CaTiO3 and, more importantly, its dielectric response process is clarified. Through combined HAADF‐STEM, DFT calculation, dielectric, and photoluminescence (PL) spectroscopy, the defect configuration is identified to be VCa − O− − LaCa type defect‐cluster‐dipole. The electron–hole recombination from the Ti3+ and O− states dominates the dielectric relaxation process, as revealed by the similar relaxation frequencies of dielectric response and photoluminescence emission. These findings experimentally demonstrate property tailoring involved in defect‐cluster‐dipole, providing crucial insights for establishing the defect‐property relationship in dielectric materials. In La‐doped CaTiO3, the clustering of La ion and Ca vacancies is clearly observed and the configuration of such defect‐cluster is validated. Combining photoelctronic and dielectric spectroscopy enables the dielectric relaxation process with the charge transfer routes. The results provide a clear picture of how the defect‐dipole forms and leads to enhanced permittivity in perovskite oxides.